THE EFFECT OF USING POINT COUNTER POINT STRATEGY ON STUDENTS' SPEAKING ABILITY (A STUDY AT THE TWELFTH GRADE STUDENTS OF SMA NEGERI 1 BATANG ONANG IN 2020/2021 ACADEMIC YEAR) - rotua purba (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The purposes of this research are to know: 1) the application of point counter point strategy on teaching speaking ability, 2) the students’speaking ability before and after using point counter point strategy, 3) Whether there is any significant effect of point counter point strategy on teaching speaking ability at the twelfth Grade Students of SMA Negeri 1Batang Onang. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the XII grade students’ of SMA Negeri 1Batang Onang which consist of 175 students. Sample were XII MIA 1 which consist of 24 students which taken by purposive sampling. In collecting data the researcher uses observation sheet and oral test as an instrument. The result of this research: 1) the application of point counter point strategy was 3.7, it was categorized “Very Good”. 2) the mean score of the students’ speaking ability was 39 and it was categorized “fail”. Meanwhile, after using point counter point strategy was 63, it is categorized “enough”. The result of data analysis shows that ttest was higher than ttable(ttest22.38>ttable2.07). So, the hypothesis was accepted. It means that, there is any significant effect of point counter point strategy on students’ speaking ability at the XII grade students of SMA N 1Batang Onang. Keywords: Point Counter Point Strategy, Speaking Ability